Ibnu Khaldun's Concept of Education and Its Relevance With Educational Psychological Figure - Shopiah Syafaatunnisa; Muhibbin Syah; Bambang Samsul Arifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to explore the relevance of Ibn Khaldun's educational ideas with the theories of several educational psychology figures. It is a qualitative study utilizing literature review methods. The results indicate a connection between Ibn Khaldun's educational concepts and figures in educational psychology such as Wolfgang Kohler, Kohlberg, Herbert Spencer, Montessori, John Amos Comenius, William Stren, and Piaget. This further demonstrates that Ibn Khaldun's expertise has transcended his time, as modern education incorporates many concepts that were formulated by this thinker who lived in the 14th century, long before the current modern era.